2021
DOI: 10.1097/md.0000000000024154
|View full text |Cite
|
Sign up to set email alerts
|

Effect of education and muscle relaxation program on anxiety, depression and care burden in caregivers of acute stroke survivors

Abstract: This study intended to discover the effect of education and muscle relaxation (EMR) program on anxiety, depression and care burden among caregivers of acute stroke survivors. This randomized, controlled study enrolled a total of 110 caregivers of first-ever acute stroke patients, and randomly assigned to EMR (N = 55) and control (N = 55) groups. The caregivers in the EMR group received 12-month health education and progressive muscle relaxation, and those in control group were provided common rehabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 18 publications
1
41
0
3
Order By: Relevance
“…Studies that combined skilled building with psychoeducation in this review provided the most positive caregiver and survivor outcomes. 19,20,26,28,32…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies that combined skilled building with psychoeducation in this review provided the most positive caregiver and survivor outcomes. 19,20,26,28,32…”
Section: Discussionmentioning
confidence: 99%
“…24 Caregiver anxiety and depression were measured in 5 studies using the Hospital Anxiety and Depression Scale. [24][25][26]28,29 Other anxiety and depression measures included the Center for Epidemiological Studies Depression Scale, 19,21,30 Patient-Reported Outcomes Measurement Information System-Depression Short Form 8b, 35 Patient Health Questionnaire-9, 31 Beck Depression Scale, 27 Zung Self-rating Anxiety Scale, 28 and the Zung Self-Rating Depression Scale. 28 Several studies measured caregiver health-related quality of life using the same measures that were used for stroke survivors (ie, Older People's Quality of Life Questionnaire, 35 the Satisfaction with Life Scale, 32 and the EuroQol European Quality of Life EuroQol 24,25 ).…”
Section: Measurement Of Caregiver Outcomesmentioning
confidence: 99%
“…A study on the FCGs of patients with dementia also showed the positive effects of SM on PSS (35). Moreover, a study found that health education programs significantly improved social health among the FCGs of PWS (36). PSS among the FCGs of patients with epilepsy and PWS has significant direct relationships with their SM ability, quality of life (35), and mental health (37).…”
Section: Discussionmentioning
confidence: 99%
“…However, anxiety and depression are not independent variables, as the literature shows a correlation between them; anxiety is a predictor of depression. In combination, both are variables associated with a more significant burden and lower quality of life in the caregiver (17,18).…”
Section: Introductionmentioning
confidence: 99%